2006
DOI: 10.1542/peds.2005-1215
|View full text |Cite
|
Sign up to set email alerts
|

How Does Maternal and Child Feeding Behavior Relate to Weight Gain and Failure to Thrive? Data From a Prospective Birth Cohort

Abstract: Inherent child appetite characteristics seem to be an important risk factor for weight faltering and failure to thrive, but high maternal promotion of feeding may also have an adverse influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 23 publications
5
128
0
1
Order By: Relevance
“…There were no major differences between traits; a larger appetite rating, greater enjoyment of food, greater food responsiveness, faster eating speed, and lower satiety responsiveness were all related to higher weights and faster weight gains over 6-and 12-mo periods during infancy. These findings were in line with other studies that have investigated associations between infant appetite and weight gain in early childhood (15,17).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There were no major differences between traits; a larger appetite rating, greater enjoyment of food, greater food responsiveness, faster eating speed, and lower satiety responsiveness were all related to higher weights and faster weight gains over 6-and 12-mo periods during infancy. These findings were in line with other studies that have investigated associations between infant appetite and weight gain in early childhood (15,17).…”
Section: Discussionsupporting
confidence: 92%
“…Answers were on a 5-point scale (ie, poor, okay, good, very good, or excellent), and higher scores indicated a larger general appetite (17).…”
Section: Appetitive Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, only between 5 and 10% will have any symptoms or signs of underlying disease (14) . Some evidence of differences in maternal feeding behaviour and appetite and eating behaviour as well as decreased energy intake at meals (31) have been found in the infant (27)(28)(29)(30) . Thus, the majority of children showing a weight faltering pattern have no observable disease or evidence of neglect.…”
Section: Failure To Thrive/weight Falteringmentioning
confidence: 99%
“…1 Feeding difficulties are known to impact on weight gain, with a high percentage of children suffering from concomitant growth faltering, which may have a long-term effect on longitudinal growth and cognitive development. [2][3][4] For many years, it has been known that some medical conditions in early infancy may lead to feeding difficulties. Levy et al 5 found in children with organic disease that, in addition to the size of the child, transition in feeding (i.e.…”
Section: Introductionmentioning
confidence: 99%